The intensification impact of dairy cattle breeding on the beef production development in the Russian Non-Chernozem zone - V. V. Smirnova (Вестник университета)
The dairy cattle breeding role in the economy of the Non-Chernozem zone is historically great, therefore, the development analysis of this industry with the intensive technologies use is an urgent task.   The study purpose is to identify the causes of stagnation in beef production with positive dynamics in the dairy industry.   The paper examines the dynamics of increasing the cows’ productivity by region; the concentration process of milk and cattle meat production. The intensity assessment of production in the young dairy breeds’ fattening is given. Research methods include economic and statistical analyses, as well as comparison. The change in the placement of dairy cattle breeding has been revealed: new large-scale projects are being built in the Chernozem zone and in the regions of the Non-Chernozem zone with high grain yields. Approaches to stimulating beef production in the current conditions at the regional level are considered. The state regulation expediency of the dairy and beef cattle breeding placement has been substantiated.